PENERAPAN SISTEM TRANSFORMASI DIGITAL-ANDRAGOGI MELALUI MEDIA GOOGLE SITES PADA KELOMPOK KERJA PENYULUH AGAMA HINDU DENPASAR TIMUR KEMENTERIAN AGAMA KOTA DENPASAR - Kadek Dwi Sentana Putra Dwi Sentana Putra (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2022)
The East Denpasar Hindu Extension Working Group is a working team from the Ministry of Religious Affairs of Denpasar City that provides counseling to the community in the East Denpasar region, through the Sad Dharma method and through the Google Sites application owned today. Sad Dharma is a form of service to the community through the extension of Hinduism with the approach of the pattern of "sharing and caring", all communities approach andragogi through learning together through digital media one of them with google sites provided by the working group of Hindu extensionists, but in the process of application there are still obstacles - obstacles one of which is the way of ngakses for some village areas built by Hindu extension groups.  Therefore, researchers are very interested in conducting research that has to do with non-formal class action research in society through a digital-based andragogy approach no longer just with traditional or traditional. The formulation of the problem in this study is how it is implemented, are there obstacles and how the solution is offered. The method used is a mixture of proportions of sampling into snowball sampling. The result of this research is a Form of Sad Dharma that is revised with google sites, there are internal and external constraints and the solution undergoes communication through the Whatsaapp group and provides instructions on the home halam on google sites belonging to hindu religious extensionists in east Denpasar.